Morphological and molecular characterization of some popular cultivated mushrooms of India - Kumar, Sanjeev (Mushroom Research, 2022)
Morphological and molecular characterization of some popular cultivated mushrooms of IndiaSanjeev Kumar1*, Anand Sagar2, Shwet Kamal3 and Jagriti Rana41. Associate professor, Govt. College Bilaspur.2. Dean of Life Sciences, H.P. Univ.. Shimla.Â 3. Principal Scientist, DMR Solan.4. PhD research Scholar, Department of Biosciences, H.P. Univ.Shimla.* Corresponding author, E-mail: sanjeev5112@gmail.com +919418045021Â AbstractThe mushroom cultivation is a highly lucrative agribusiness to produce nutritious food and earn money in short space and time. The present studies were conducted to analyze morphological and molecular characteristics of five cultivated strains of mushrooms Agaricus bisporus (NBS-5), Calocybe indica (DMRO-302), Flammulina velutipes (DMRO-253), Pleurotus florida (DMRP-136) and Volvariella volvacea (DMRO-484). The fruiting bodies were procured from ICAR-Directorate of Mushroom Research, Solan, HP (India) and screened for morphological and molecular details. Macroscopic features like shape, size and colour of stipe and pileus were recorded. Microscopic details were worked out by cutting free hand sections of material and observed under research microscope and scanning electron microscope. Molecular identification was done through internal transcribed spacer (ITS) regions of ribosomal DNA sequencing. The nucleotide sequences of each sample were analyzed for Basic local Alignment Search Tool (BLAST) search program in US National Centre for Biotechnology Information (NCBI) for identification. The DNA sequences obtained in this study were submitted in the Gen Bank database at NCBI with accession numbers MW718994.1 (A. bisporus), MW714627.1 (C. indica), MW719474.1 (F. velutipes), MW719254.1 (P. florida) and MW720603.1 (V. volvacea).Keywords: Mushroom, Molecular identification, ITS, rRNA, Nucleotide sequencing, Gen Bank database